2013
DOI: 10.1371/journal.pone.0060532
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Complex Interventions on Depression and Anxiety in Chronic Obstructive Pulmonary Disease: Systematic Review and Meta-Analysis

Abstract: BackgroundDepression and anxiety are very common in people with chronic obstructive pulmonary disease (COPD) and are associated with excess morbidity and mortality. Patients prefer non-drug treatments and clinical guidelines promote non-pharmacological interventions as first line therapy for depression and anxiety in people with long term conditions. However the comparative effectiveness of psychological and lifestyle interventions among COPD patients is not known. We assessed whether complex psychological and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
109
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(126 citation statements)
references
References 85 publications
7
109
0
4
Order By: Relevance
“…Other studies including one with a waiting list as the control group failed to find significant effects. In line with these findings, a recent meta-analysis revealed only small, nonsignificant effects of CBT on self-reported symptoms of depression in COPD patients [63]. In comparison to COPD education, CBT has been shown to have a comparable antidepressant effect [64].…”
Section: Effects Of Psychotherapymentioning
confidence: 84%
“…Other studies including one with a waiting list as the control group failed to find significant effects. In line with these findings, a recent meta-analysis revealed only small, nonsignificant effects of CBT on self-reported symptoms of depression in COPD patients [63]. In comparison to COPD education, CBT has been shown to have a comparable antidepressant effect [64].…”
Section: Effects Of Psychotherapymentioning
confidence: 84%
“…Furthermore, in one randomized clinical trial in patients with COPD and depression, a personalized outpatient intervention program composed of education and counseling improved not only depressive symptoms and adherence to antidepressants, but also dyspnea-related disability (43). Pulmonary rehabilitation can modify both depression symptoms and readmission rates (44,45), but whether there is a causative link between reduction in depression scores and readmission rates has not been tested. In a retrospective analysis of Medicare data, Ahmedani and colleagues showed that patients with congestive heart failure, pneumonia, and acute myocardial infarction experienced increased risk of 30-day hospital readmission in the presence of comorbid depression (46).…”
Section: Original Researchmentioning
confidence: 99%
“…cognitive behaviour therapy) have also been used in this same population to manage anxiety, depression, QOL, [5][6][7][8][9][10][11] dyspnoea 12 and exercise tolerance. 13 Over the last decade, four systematic reviews (with and without meta-analysis) have examined the evidence base for psychologically based interventions to alleviate anxiety and depression in people with COPD [14][15][16][17] with one systematic review for adults with asthma. 18 These reviews variously concluded that there was insufficient, 17,18 limited 14,16 and sufficient evidence 15 to support the use of psychological interventions.…”
Section: Introductionmentioning
confidence: 99%
“…13 Over the last decade, four systematic reviews (with and without meta-analysis) have examined the evidence base for psychologically based interventions to alleviate anxiety and depression in people with COPD [14][15][16][17] with one systematic review for adults with asthma. 18 These reviews variously concluded that there was insufficient, 17,18 limited 14,16 and sufficient evidence 15 to support the use of psychological interventions. Each of these reviews included studies where psychological interventions may have been provided in combination with exercise training, and (with the exception of Coventry et al 15 ) did not undertake subgroup analyses to compare different forms of interventions.…”
Section: Introductionmentioning
confidence: 99%